Assessing VOC Emission by Wood Pellets Using the PTR- ToF-MS Technology - C. Costa; C. Taiti; M. Zanetti; A.R. Proto; S. D'Andrea; R. Greco; L. Dematte; S. Mancuso; R. Cavalli (Chemical Engineering Transactions, 2017)
Wood pellets are important fuel in heat and power production with a high potential to grow in the future. Pellets represent a well spread commodity for energy production in Europe with a rapidly increasing market. To analyze the Volatile Organic Compounds (VOCs) emitted from wood pellets, 21 samples have been collected in triplicate. Seventeen samples are commercial pellets and 4 are pellets produced at laboratory scale. Based on the in-force ISO standard, the commercial pellets belong to the high-quality classes A1 and A2. To analyse Volatile Organic Compounds (VOCs) emissions, each sample were introduced in a glass jar connected to PTR-TOF 8000 (Ionicon Analytik GmbH, Innsbruck, Austria) and each one analyzed with a zero-air generator. The tool was set in the standard configuration using H3O+ as proton donor in the transfer reaction. The raw data were acquired by the TofDaq software (Tofwerk AG, Switzerland) using a dead time of 20 ns for the Poisson correction, and subsequently they were converted in ppbv (part per billion by volume). A total number of 53 VOCs were selected as more informative. A multivariate ordination technique (Principal Component Analysis - PCA) were applied on the matrix 60 (pellet samples) x 53 (VOCs) in order to observe the pellet sampled in a reduced space. On the negative side of the first (51.1%) and second (13.0% of the explained variance) PCA axes were positioned the samples characterized by chestnut, beech, or mixed pellets containing these wood species. The samples located close to the origin consist of a mix of different pellets samples, while the coniferous pellets were located along the positive side of PC1 and PC2. Moreover, was observed a sort of a gradient, from the negative to the positive side of the first axis and from hardwood to softwood pellet. Using the entire dataset of VOCs, it has been observed a lack of a clear distinction between groups of pellets belonging to different wood species which could be due to several reasons such as the intrinsic variability of the wood, the pellet manufacturing process (e.g., the temperature of the extruder), the addition of additives and the different geographic origin of biomass.